Implementasi Internet of Things Pada Sistem Kendali Lampu Rumah Menggunakan Telegram Messenger Bot Dan Board ESP - Wahyu Setiawan; I Made Sugi Ardana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The development of information technology in the era of the Industrial Revolution 4.0. increasingly showing its sophistication through a system designed by humans to facilitate activities in daily life. Especially IoT (Internet of Things) we often find homeowners who forget to turn off the lights or turn on the lights when leaving the house or when they are at home. This results in a waste of electrical energy. Homeowners desire where the control system becomes an automatic control system using Telegram Messenger bot and Board esp. By meeting the needs of system development, the development method used is a prototype where this development method uses an approach with the user so that it is faster and gradual so it can be evaluated by the user.Based on the analysis and testing of the system as a whole, it can be concluded that with the construction of an IoT-based lamp control controller using Telegram Messenger bot and Board esp that utilizes smartphones and internet network connections, it can assist users in controlling lights remotely, anywhere, and anytime, without having to to the switch source.